Pengaruh Cooperative Integrated Reading and Composition (CIRC) Berbantuan Mind Mapping Terhadap Hasil Belajar IPS Kelas IV SDN 35 Palembang - Zulkarnaein, Zulkarnaein; Tanzimah, Tanzimah; Ayurachmawati, Puji (ANTHOR: Education and Learning Journal, 2022)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Mind Mapping on student learning outcomes in social studies class IV SDN 35 Palembang. This type of research is experimental research with a True Experimental Design design, while the research subjects are students of class IV SDN 35 Palembang, class IV. An as the experimental class and class IV.C is the control class, each class consisting of 24 students. Methods of data collection using tests and documentation. The test instrument is in the form of multiple choice questions totaling 20 questions to measure student learning outcomes in social studies lessons. The data analysis technique uses the t-test. Based on the results of the study, the average posttest score obtained from social studies learning outcomes using the Mind Mapping-assisted CIRC learning model was 83.33 and for social studies learning not using the Mind Mapping-assisted CIRC learning model was 76.66. From testing the hypothesis obtained t_count>t_table (2.084 > 2.012), with a significant level of 0.05, it can be stated that Ho is rejected and Ha is accepted. Thus, Cooperative Integrated Reading and Composition (CIRC) assisted by Mind Mapping has an effect on social studies learning outcomes for grade IV SDN 35 Palembang for the 2021/2022 academic year.